Clinical Observation of Modified Implantation of ASD Closure Device to Treat BPFs. (12th October 2022) - Lu, Yangfei; Zhang, Jisong; Chen, Enguo; Ying, Kejing
Abstract : Objectives . The aim of the paper is to explore the clinical efficacy and prognosis of the modified implantation of atrial septal defect (ASD) closure device to treat bronchopleural fistulas (BPFs). Methods . This paper has reviewed the results of 13 BPF patients implanted with a modified ASD closure device in Shaw Hospital Affiliated with the Medical College of Zhejiang University from October 2018 to November 2021. Anesthesia was selected based on the patient's condition. Different sizes of ASD closures were selected based on the characteristics of fistulas. The modified implantation of the ASD closure device was applied to treat BPFs. The closure effects, closure time, and Borg score were observed at 4 weeks, 8 weeks, and 12 weeks after the surgery. Results . All 13 BPF patients were successfully implanted with the ASD closure device, and the immediate clinical remission rate was 100%. Follow-up at 4 weeks after the surgery showed that 2 cases were automatically discharged within a few days and 4 cases had closed fistula at 1 day after the surgery; follow-up at 8 weeks after the surgery showed that 1 case with fistula closure was observed at 55 days after the surgery; follow-up at 12 weeks after the surgery showed that 1 case with fistula closure was observed at 82 days after the surgery. T/ P values ( T  = 7.90, 5.99, 7.44, P < 0.05 ) of paired t -tests before surgery and 4 weeks, 8 weeks, and 12 weeks after the surgery were rated by the Borg scale. The data were statistically different, and the clinical symptoms improved significantly. As of publication, the follow-up at 12 weeks after the surgery showed that the clinical remission rate was 9/11, namely, 81.8%, 3 of 11 cases had relieved clinical symptoms but still needed continuous drainage, and 2 cases had fistula closure. The median time of thoracic extubation was 63 (3, 120) days. No patients died from surgical complications or BPF recurrence during the prognosis and the follow-up period. Conclusions . The modified implantation method has a high success rate and clinical remission rate, quick and early fistula closure, and simple and noninvasive operation, without the need for a dedicated delivery sheath and rigid endoscopy. Moreover, it has accurate positioning, reliable closure efficiency, and prognosis, and can be completed under local anesthesia. This reduces the operation time, difficulty, and risks of anesthesia.